The efficacy of Clorhexidine 0.2% after scaling in marginal gingivitis - M Shahrohisham; Widowati Witjaksono (Dental Journal (Majalah Kedokteran Gigi), 2005)
Thirty male subjects aged around 20-30 years old, with complete anterior teeth, no inter proximal caries and good general health conditions were selected by using simple random sampling. The anterior teeth were divided into 2 segments right side for 11, 12, 13 and left side for 21, 22, and 23. These two sites were treated by different way for comparing two treatment variables, between scaling therapy alone and scaling therapy with adjunction of Chlorhexidine (CHX) 0.2%. Gingival Index (GI) score was used to determine the gingivitis status of the subjects. Clinical experiment showed that the duration of healing process in subjects treated with scaling with adjunction of CHX 0.2% was faster than scaling therapy alone group. However, in the statistical analysis, there was no significant difference because of several factors. In conclusion, it was found that CHX 0.2% had the efficacy to enhance the healing process in the marginal gingivitis patient that was treated by scaling therapy, but further study using CHX 0.2% with longer duration time should be done to achieve more pronounce effect